The library of Mr. & Mrs. Neutra - Khonsary, Jeff 1979-; Critton, Benjamin (New Documents, 2022)
"The Library of Mr. & Mrs. Neutra" uses the built environment of Richard and Dione Neutra's VDL House (1932/1965) as a space for site-specific research into the content and material structure of the modernist architect's library. Working to document the volumes collected in the Los Angeles residence and studio's extensive library, this book indexes the specific, lived history of a personal book collection marked by its owner's professional, personal, and familial relationships.
Impressum: "The Library of Mr. & Mrs. Neutra" was published on the occasion and exhibited as a part of "Built In" at the Neutra VDL House II, September 17 - November 7, 2021
Edition of 500
Keywords: Neutra, Dione -- 1901-1990; Neutra, Richard -- 1892-1970; Bibliothek; Buch; Ausstellungskatalog -- Neutra VDL House II -- 17.09.2021-07.11.2021 -- Los Angeles, Calif.; Inventar